Bond coupons issued by the city of Savannah, Ga. - Savannah (Ga.)
Bond coupons issued by the city of Savannah, Ga. It appears that the bonds have been redeemed.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Bonds -- Georgia -- Savannah